Smart self-sensory TRC pipes—proof of concept. (1st May 2022) - Perry, Gali; Goldfeld, Yiska
Abstract: The paper aims to prove the feasibility of smart concrete pipe systems with integrated monitoring capabilities. The development of such systems is motivated by functional, structural, sustainability and monitoring requirements of underground and buried pipelines with limited accessibility. To answer these challenges, the study adopts the textile reinforced concrete (TRC) technology that allows the production of effective, durable, and lightweight structural elements with integrated monitoring systems. In such systems, by utilizing the electrical conductivity of the carbon rovings, the carbon-based textile can simultaneously serve as the main reinforcement system and as the sensory agent. The proposed hybrid monitoring system aims to detect the occurrence of leakage and to distinguish its severity, which is directly correlated to the structural health. Smart TRC pipes were designed, constructed, and experimentally investigated from structural and sensory points of view. The design considers the multifunctionality of the carbon rovings and the hybrid performance of the textile cage, from both aspects—reinforcement and sensing. An experimental investigation explores the mutual structural, functional, and sensory capabilities of the hybrid system, which reflect and affect each other. It is presented that the strong correlation between the structural-functional and sensory responses reveals an efficient smart TRC pipes. The presented results take a major step toward the realization of the smart TRC concept and exceeded beyond small 1D scale elements to 3D structures.